(untitled) (Studies in ELT and Applied Linguistics, 2021)
This article proposes SQC framework for English language education. The meaningful context in which the language activities take place as the students work through the cycle of problem solving provides rich opportunity to develop their language skills. Theoretical, conceptual and historical background and framework, stages of SQC case study, tools and techniques used in problem solving to develop the students’ personality, language and SQC interface and sample SQC case study have been discussed in this paper. The potential of SQC leading to TQC for professional development and its potential to inform and refine the ELT curriculum has been proposed. The systematic and scientific approach that SQC adopts has tremendous future potentials in academia.